Low free triiodothyronine levels are associated with frail phenotype in hospitalized inpatients with cirrhosis. Issue 5 (4th July 2022) - Li, Chaoqun; Zhao, Chunshan; Yu, Zihan; Yang, Wanting; Sun, Mingyu; Li, Yifan; Guo, Gaoyue; Hui, Yangyang; Wang, Xiaoyu; Fan, Xiaofei; Wang, Bangmao; Zhang, Jie; et al.
ABSTRACT: Objective: Frailty is a prevalent complication predicting morbidity and mortality in cirrhosis. However, the association between thyroid hormone levels and frailty in cirrhotics remains elusive. Therefore, we aimed to evaluate the relationship between thyroid hormone and frail phenotype in euthyroid patients with cirrhosis. Methods: A total of 214 adult cirrhotic inpatients were divided into two groups according to Frailty Index. Concentrations of free triiodothyronine (FT3), free thyroxine (FT4) and thyroid stimulating hormone (TSH) were compared. An analysis of the receiver operating characteristic (ROC) curve was implemented to determine the best cutoff for frailty. Multiple logistic regression was used to assess the association between FT3 and frailty. Results: ROC analysis indicated that the optimal cutoff to stratify frailty was FT3 < 3.03 pmol/L with an area under the curve of 0.673 (95% CI: 0.582–0.764, p = 0.002), sensitivity of 81.8%, and specificity of 51.9%. Patients with FT3 < 3.03 pmol/L exhibited higher incidence of Child-Pugh class B/C, elevated model for end-stage liver disease score, higher creatinine, lower sodium as well as higher incidence of frailty (23.7 vs 6.0%, p < 0.001). A negative correlation was observed between FT3 values and Frailty Index (r = −0.220, p = 0.001). FT3 remained an independent risk factor for frailty after adjusting for age, Child-Pugh class, creatinine, sodium, and alanine aminotransferase. Conclusion: In our current study, FT3 < 3.03 pmol/L were significantly associated with increased risk for frailty. Measuring FT3, a readily available biomarker, may be useful for identifying frail phenotype in euthyroid patients with cirrhosis.